Emirati youth empowerment through small and micro enterprises: (A field study) - Hassan, Sharifa Mohammed; Alhourani, Mohammed (Al-Adab Journal, 2023)
The important role of micro and small enterprises is evident. These enterprises leave their marks on the economic scene due to their strategic importance in re-engineering the industrial, commercial and production sectors, achieving development and supporting the economy, as well as their role in empowering members of society, including the youth. Empowering youth and overcoming all obstacles to benefit from their energies and creativity represents a sustainable national vision for the United Arab Emirates. This study aimed to identify the views of the youth beneficiaries of these funds and institutions and their effectiveness. Accordingly, seven research questions were formulated to answer them. The study used the quantitative approach, where quantitative data was collected through the use of a questionnaire distributed to (503) young people benefiting from projects supported by institutions and funds. The study also revealed a number of challenges and problems facing young entrepreneurs and support institutions and funds. Finally, the study recommended a number of points that can contribute to raising the level of youth empowerment in UAE, including revising the current policies and establishing a comprehensive system for youth empowerment in which all parties in society participate, provided that this system includes facilitating procedures for establishing youth enterprises and enhancing youth skills of entrepreneurship and project management.